Severity, change over time, and risk factors of anxiety in children with cancer depend on anxiety instrument used. Issue 4 (12th February 2019) - Lazor, Tanya; Pole, Jason D.; De Souza, Claire; Schechter, Tal; Grant, Ronald; Davis, Hailey; Duong, Nathan; Stein, Eliana; Cook, Sadie; Tigelaar, Leonie; Sung, Lillian
Abstract: Objective: The primary objective was to describe severity of anxiety among children and adolescents receiving chemotherapy for cancer or undergoing hematopoietic stem cell transplantation (HSCT). Secondary objectives were to describe how anxiety changes over time and determine factors associated with anxiety. Methods: Participants were aged 8 to 18 and either receiving chemotherapy for cancer or undergoing HSCT for any indication. Respondents self‐reported three anxiety measurement instruments at chemotherapy cycle or HSCT conditioning start and 3 weeks later. Results: The proportion of participants with severe anxiety ranged from 10/77 (13.0%) to 22/77 (28.6%) depending on instrument used. Change over time also varied across instruments, with significant improvement observed with PedsQL (procedural) ( P = 0.037) and PROMIS ( P = 0.013). Factors associated with anxiety similarly varied by instrument. Older age was associated with more anxiety on the PedsQL (worry) ( P = 0.036), and higher household income was associated with less anxiety on the MASC‐10 ( P = 0.028). Conclusions: While we found that a small proportion of patients met or exceeded thresholds for severe anxiety, we also noted that severity, change over time, and predictors of anxiety varied depending on instrument used. Future research should ensure that selected instruments measure the construct of interest and describe how anxiety is conceptualized in the study.